Hypothalamic inhibition of neurones in the nucleus tractus solitarius of the cat is GABA mediated. - Jordan, D (1988)
1. In pentobarbitone-anaesthetized cats extracellular activity of neurones in the vicinity of the nucleus tractus solitarius receiving inputs from the carotid sinus nerve (SN) and/or vagus nerve (VN) during stimulation of the hypothalamic defence area (HDA) and application of gamma-aminobutyric acid (GABA) and glycine and their antagonists have been studied. 2. A total of forty neurones have been tested, of which twenty-four only had an input from the SN, one only from the VN, twelve from both nerves and three had neither SN or VN inputs. 3. Short trains of stimuli to the HDA inhibited both the ongoing activity (if present) and evoked discharge in thirty-nine of the forty neurones tested. 4. In the forty cells tested ionophoretic application of GABA reduced (4) or totally inhibited (35) neuronal discharge whilst in the thirty-eight tested with glycine discharge was totally (25) or partially (12) suppressed. 5. Ionophoresis of bicuculline totally (14) or partially (6) antagonized the inhibitory actions of GABA in the twenty-five cells tested, and in eighteen of these the ongoing and/or evoked activity was simultaneously increased. In eighteen of the nineteen cells tested this level of bicuculline also antagonized the inhibitory actions of HDA stimuli whereas in none of the sixteen cells tested did it affect glycine-evoked inhibitions. 6. Ionophoretic application of strychnine antagonized the inhibitory effects of glycine in eight of nine cells tested but in these eight cells strychnine had no effect on ongoing or evoked discharges, GABA- or HDA-evoked inhibitions. 7. In a chloralose-anaesthetized cat five neurones receiving SN inputs (three also receiving VN inputs) were recorded. All could be inhibited by HDA stimuli and by application of GABA. In the three of four cells in which bicuculline antagonized GABA inhibitions, the effects of HDA stimuli were simultaneously antagonized whereas glycine-evoked inhibitions were unaffected. 8. In two neurones, in addition to inhibiting neuronal discharge HDA stimulation also evoked activity in the cells. In a further four neurones similar excitatory responses were uncovered when the HDA inhibitory effects were antagonized by bicuculline. 9. The importance of these observations in cardiovascular control and in the functioning of the baroreceptor reflex is discussed.